Strengthening Pre-Service IRE Teachers’ Character in University Settings Based on the Student Regiment (Menwa) Organization - Salsabila, Almas Tsuroyya; Syahidin; Parhan, Muhamad (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2025)
The role of Islamic Religious Education (IRE) teachers requires not only pedagogical proficiency but also strong character and mastery of four core competencies, namely personality, social, professional, and pedagogical competencies. However, the contribution patterns of semi-military extracurricular organizations, such as the Student Regiment (Menwa), to the development of competencies among pre-service IRE teachers have not yet been systematically mapped. This study aims to analyze the thematic patterns of Menwa’s contribution to character formation and the development of the four core competencies of pre-service IRE teachers. The study employs a Systematic Literature Review (SLR) method following the PRISMA 2020 guidelines by synthesizing findings from ten relevant articles. The synthesis results indicate varying levels of contribution across competencies. Personality and social competencies emerge as the most dominant aspects, characterized by the internalization of discipline, responsibility, nationalism, and leadership through experiential learning, habituation, and exemplary practices (uswah ?asanah). In contrast, contributions to pedagogical and professional competencies are indirect, primarily manifested through leadership experiences, systematic communication, decision-making processes, and the formation of work ethic and resilience. Nevertheless, most studies identify limitations in the integration of Islamic values due to the dominance of physical-oriented approaches and command-based patterns. In conclusion, Menwa functions as an effective social laboratory for developing the non-cognitive competencies of pre-service IRE teachers, although strengthening the integration of spiritual values remains necessary